Brief Report: Efficacy and Safety of Efavirenz, Raltegravir, and Dolutegravir in HIV-1/TB Coinfection. A Multicenter Retrospective Cohort Study in France. (1st September 2022) - Kherabi, Yousra; de Castro, Nathalie; Sellier, Pierre-Olivier; Hamet, Gwenn; Brun, Alexandre; Méchaï, Frédéric; Joly, Véronique; Yazdanpanah, Yazdan; Molina, Jean-Michel
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: There are limited data comparing the efficacy and safety of raltegravir and dolutegravir to that of efavirenz in HIV-1/tuberculosis (TB) coinfected patients. Methods: We conducted a 10-year retrospective study in 4 centers in France. We included all HIV-1/tuberculosis coinfected patients starting antiretroviral therapy with a rifampicin-based regimen, with a plasma HIV RNA level (VL) > 1000 copies/mL. The primary endpoint was the proportion of patients with virological success that is, with VL <50 copies/mL at W48 using an Intention-To-Treat analysis, using last-observation-carried-forward to impute missing data. We also assessed antiretroviral therapy safety, analyzing treatment discontinuation for adverse events. Results: Between 2010 and 2020, 117 patients were included. Thirty-nine (33.3%) were treated with raltegravir and 2 nucleoside reverse transcriptase inhibitors (NRTIs), 19 (16.2%) with dolutegravir (and 2 NRTIs) and 59 (50.4%) with efavirenz (and 2 NRTIs). At W48, the primary endpoint was achieved in 24 patients (61.5%) in the raltegravir group, in 12 (63.2%) in the dolutegravir group, and in 41 (69.5%) in the efavirenz group using an Intention-To-Treat analysis ( P = 0.68). Emergence of drug resistance in patients with virological failure, defined as a VL >50 copies/mL, was observed in 3 patients with efavirenz and one patient with raltegravir. Rate of treatment discontinuation for drug-related adverse events was 10.3%, 10.6%, 16.9% for raltegravir, dolutegravir and efavirenz respectively ( P = 0.67). Conclusions: In this retrospective cohort study, raltegravir and dolutegravir yielded similar efficacy and safety results to efavirenz for the treatment of HIV-1/TB coinfected patients.